2011
DOI: 10.1016/j.jstrokecerebrovasdis.2009.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Altered Neural Activity and Emotions Following Right Middle Cerebral Artery Stroke

Abstract: Background and Purpose-Stroke of the right MCA is common. Such strokes often have consequences for emotional experience, but these can be subtle. In such cases diagnosis is difficult because emotional awareness (limiting reporting of emotional changes) may be affected. The present study sought to clarify the mechanisms of altered emotion experience after right MCA stroke. It was predicted that after right MCA stroke the anterior cingulate cortex (ACC), a brain region concerned with emotional awareness, would s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 69 publications
(83 reference statements)
1
23
0
Order By: Relevance
“…Subjects were selected from a larger cohort recruited to study brain networks effects of focal brain damage during emotion experience using PET and the [ 15 O]water method (Paradiso et al, 2003; Turner et al, 2007; Paradiso et al, 2011). Subjects with stable strokes to the LBG (i.e., time from acute stroke greater than 3 months), confirmed by neurological exam and MRI scan (Figure 1), constituted the experimental group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjects were selected from a larger cohort recruited to study brain networks effects of focal brain damage during emotion experience using PET and the [ 15 O]water method (Paradiso et al, 2003; Turner et al, 2007; Paradiso et al, 2011). Subjects with stable strokes to the LBG (i.e., time from acute stroke greater than 3 months), confirmed by neurological exam and MRI scan (Figure 1), constituted the experimental group.…”
Section: Methodsmentioning
confidence: 99%
“…Brain activity elicited by viewing emotional and neutral stimuli and measured using [O 15 ]water positron emission tomography (PET) (Turner et al, 2007; Paradiso et al, 2008a; Paradiso et al, 2011) is reported in individuals with LBG damage relative to healthy volunteers. Because idiopathic (i.e., depression without gross brain damage) and post-stroke depression (Paradiso et al, 1997a) show essentially overlapping phenomenology, it was expected that depression following LBG lesion would be associated with the characteristic patterns of brain activity observed in idiopathic depression including higher activity in amygdala and mesial prefrontal cortex and lower activity in dorsal lateral prefrontal cortex (Drevets, 2001; Mayberg, 2002; Zhong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researches had, in general, administrated screenings such as the Mini Mental State Exam -MMSE (14) , some tasks of expanded batteries (15) or entire expanded batteries (13) . Therefore, seems to be an even larger gap in the literature on the relationship between stroke, suggestive signs of depression (SSD) and hemispheric specialization with the processing of several cognitive functions measured by brief neuropsychological batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50% of patients with right hemisphere damage (RHD) have some kind of acquired communication disorder (1) , which can affect social interactions and thus pose psychosocial and functional difficulties for these people (4) . The alterations in communication include: difficulties in maintaining the topic of the conversation (7) , prosodic processing (8) and understanding metaphors (1) , for example. Therefore, it is important to evaluate communication competences in addition to language skills, not infrequently ignored when it comes to RHD patients, as they exhibit appropriate language skills (phonology, semantics, syntax, morphology), but alterations, including pragmatic communication (figurative language, metaphors, jokes) and prosody, which are very important in the social context (8) .…”
Section: Introductionmentioning
confidence: 99%